MÔ HÌNH THẤM NƯỚC MƯA PHỤC VỤ PHÂN TÍCH ỔN ĐỊNH SƯỜN DỐC KHU VỰC THỊ TRẤN CỐC PÀI - HUYỆN XÍN MẦN - TỈNH HÀ GIANG - Hoàng, Nguyễn Văn; Khang, Ứng Quốc (Vietnam Journal of Earth Sciences, 2011)
Rainwater infiltration modelling for slope stability analysis in Coc Pai town-Xin Man distict-Ha Giang province Rainfall plays an important role in formation of landslides by substantially changing the physico-mechanical properties of the soil such as soil weight, cohesion, friction angle, pore water pressure etc. For a given soil, those parameters are functions of soil moisture. Raiwater infiltration makes the change in soil moisture in space, especialliy in the depth and in time. One specific rainfall event shall give a specific rainwater infiltration and moisture distribution and therfore creates a specific distribution of physico-mechanical properties. Numerical moisture movement under given rainfall event whould give a precise moisture ditribution in soil and therefore can effectively serve the slope stability analysis and prediction. Rainwater infiltration and soil moisture movement modeling for the peak rainfall event in 2008 in Coc Pai town, Xin Man district, Ha Giang province has been carried out, which provides an important input for effective slope stability analysis and prediction of the area.